A álgebra linear das matrizes no estudo da dinâmica de um braço robótico articulado - Sampaio, Hélio Luiz Oliveira (2025)
This text aims to propose an interdisciplinary approach to the study of matrices, with an emphasis on the mathematical formulation of an articulated robotic arm model. Using basic concepts from linear algebra — especially the study of matrices associated with linear transformations, homogeneous coordinates, eigenvalues, and eigenvectors — we present the main matrix properties applied to the model of a simple robotic arm with a single degree of freedom, consisting of a base and a straight arm, subjected to rigid translation and rotation movements around an axis. Finally, we propose a pedagogical intervention in high school, motivated by the need to facilitate the understanding of the presented robotic model. With the aid of the GeoGebra software, students were able to establish connections between theoretical knowledge and practical applications related to matrix content, promoting more meaningful and integrated learning.